RANCANG BANGUN PROTOTYPE APLIKASIPENGELOLAAN DATA KEUANGAN DAN JAMAAH MASJID AGUNG JAWA TENGAH MENGGUNAKAN CODEIGNITER (Information Technology and Telematics, 2014)
Abstract -- Masjid AgungJawa Tengah is a large mosque in Central Java community pride that congregation in the thousands. The mosque is not only providing a place of worship for the congregation facilities, but also provide the facility socio-economic, health, and education that aim to have a mosque worshippers feel whole. This study aims to help administrators manage data performance congregation mosque and manage financial data, which is often in the spotlight of society in terms of transparency regarding donations of funds given by donors mosque. Thus, indirectly, the management of the mosque are trying to convey financial information mosque to increase its credibility and success of the organization. In this study, financial data and build applications worshipers of the Great Mosque of Central Java using the prototyping process model and its implementation using CodeIgniter framework, as an alternative solution in order to increase accountability and improve financial management services to the congregation / community.Keywords: mosque, financial data management and jamaat, prototype, codeigniter